2023
DOI: 10.1002/uog.26170
|View full text |Cite
|
Sign up to set email alerts
|

Adverse outcome following selective termination of presenting twin vs non‐presenting twin

Abstract: What are the novel findings of the work?Selective termination of the presenting twin in dichorionic diamniotic twin pregnancy was associated with a higher rate of adverse outcome, including postprocedure complications and pregnancy loss, compared with termination of the non-presenting twin. What are the clinical implications of the work?When a discordant fetal anomaly is diagnosed in a dichorionic diamniotic twin pregnancy, management options should be discussed with the parents. If selective termination is ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(24 reference statements)
0
1
1
Order By: Relevance
“…Multiple studies have provided evidence on the impact of the position of the reduced fetus on pregnancy outcomes, indicating that reduction of the presenting fetus heightens the likelihood of miscarriage. 21,22 In our investigation, although statistical significance was not attained, a trend towards a higher rate of miscarriage was observed when the presenting fetus was reduced. This finding holds potential clinical implications, underscoring the necessity to consider the position of the reduced fetus when performing the procedures.…”
Section: Discussioncontrasting
confidence: 68%
“…Multiple studies have provided evidence on the impact of the position of the reduced fetus on pregnancy outcomes, indicating that reduction of the presenting fetus heightens the likelihood of miscarriage. 21,22 In our investigation, although statistical significance was not attained, a trend towards a higher rate of miscarriage was observed when the presenting fetus was reduced. This finding holds potential clinical implications, underscoring the necessity to consider the position of the reduced fetus when performing the procedures.…”
Section: Discussioncontrasting
confidence: 68%
“…Moreover, recent studies 26,27 report a very low rate of PPROM after amniocentesis, which precludes the prospective study of the risk of PPROM according to the entry-site location. A recent study showed that, during selective termination in twin pregnancy, the rate of early complications was higher when the presenting twin is terminated, but the gestational age at selective termination was earlier compared with that at FETO 28 .…”
Section: Findings In the Context Of What Is Knownmentioning
confidence: 99%